Gypsum composite admixture and application thereof in preparation of alpha-type high-strength gypsum
By using gypsum composite admixtures, the crystal morphology and growth of α-type semi-water gypsum is regulated, and the problem of difficulty in preparing high-strength gypsum with a single crystal transformer is solved, and an α-type high-strength gypsum product with good strength and stability is achieved.
Patent Information
- Application Number
- CN202510324068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
In the process of preparing alpha-type semi-water gypsum with pressurized hydrothermal heat, it is difficult for a single crystal transformer to obtain the alpha-type semi-water gypsum crystal form required for high-strength gypsum, and different batches of gypsum are unstable, and the crystal aggregation problem is more prominent.
A gypsum composite admixture is used, which consists of a crystal morphology regulator, a crystal growth inhibitor, a dispersant and an emulsifier. Through specific component ratios and preparation methods, a nanoemulsion-type composite solution is formed, and is prepared into a solid nanocomposite additive after spray drying.
This gypsum composite admixture can promote the growth of α-type high-strength gypsum crystal particles in a single crystal, avoid cross-growth of crystals, and obtain high-strength gypsum products with smooth morphology and uniform particle size. Its absolute dry compressive strength is ≥50MPa, and can maintain product performance stable under fluctuations in working conditions.
Smart Images

Figure CN119841566A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-strength gypsum preparation, and particularly relates to a gypsum composite admixture and application thereof in the preparation of alpha-type high-strength gypsum. Background Art
[0002] According to the industry standard JC / T 2038-2010 "α-type high-strength gypsum", α-type high-strength gypsum refers to a powdered cementitious material with α-type hemihydrate calcium sulfate as the main crystal form obtained by dihydrate calcium sulfate in a saturated water vapor medium or liquid aqueous solution under certain temperature, pressure or crystal-transforming agent conditions, and the drying compressive strength is above 25.0MPa. The synthesis methods of α-type hemihydrate gypsum currently mainly include autoclaving, pressurized hydrothermal method, normal pressure salt solution method, etc. Among them, the pressurized hydrothermal method has high efficiency in the use of admixtures, and the obtained α-type hemihydrate gypsum has good performance and great market potential. The main mechanism of the pressurized hydrothermal method is that dihydrate gypsum dissolves in the solution and then recrystallizes. The key is to control the nucleation and growth process of the crystal by controlling the composition of the solution system and the reaction conditions, so as to obtain hemihydrate gypsum crystals with the desired morphology and size.
[0003] At present, the additives added in the process of pressurized hydrothermal preparation of α-type hemihydrate gypsum mainly include organic carboxylic acids (salts), high-valent cationic inorganic salts, surfactants and macromolecular substances. Because the carboxyl group in the organic carboxylic acid (salt) will combine with the calcium ions on the end face of dihydrate gypsum to form calcium carboxylate coated on the end face, the axial growth of gypsum c is inhibited, and the aspect ratio is gradually reduced, and short columnar hemihydrate gypsum crystals with low aspect ratio can be obtained. At present, organic carboxylic acid (salt) is mainly used to regulate the crystal transformation of α-type hemihydrate gypsum. However, the effect of a single crystal transformation agent is limited, and it is difficult to obtain the α-type hemihydrate gypsum crystal form required for high-strength gypsum, so the composite crystal transformation agent technology came into being. At present, research has found that when the two types of crystal transformation agents, carboxylates and inorganic salts, act in combination, the regulation effect on the crystal growth habits is the best, and crystals with uniform size and good morphology can be obtained. Different compounding methods have obvious differences in their effects, and proper compounding can produce super-stack effects. Due to the complexity of the composite crystal-changing agent system, the absolute dry compressive strength of α-type hemihydrate gypsum prepared by the current composite crystal-changing agent technology is mostly lower than 50 MPa.
[0004] In addition, most of the current research focuses on the regulation of the morphology of α-hemihydrate gypsum crystals, while less attention is paid to the instability of different batches of hemihydrate gypsum synthesis and the agglomeration of crystals during the implementation of actual engineering projects. Therefore, it is urgent to develop new composite admixtures to improve the dispersion and uniformity of crystals, improve the stability of the synthesis process, and ensure the stability of the quality of high-strength gypsum products during the continuous operation of engineering projects. Summary of the invention
[0005] To solve the above problems, the present invention provides a gypsum composite admixture, which is used to prepare α-type high-strength gypsum, thereby obtaining hemihydrate gypsum with excellent crystallinity, dispersibility and uniformity, while ensuring the stable quality of high-strength gypsum produced continuously.
[0006] To achieve the above object, the technical solution of the present invention is:
[0007] A gypsum composite admixture comprises the following raw material components by weight: 30-50 parts of a crystal morphology regulator, 25-45 parts of a crystal growth inhibitor, 10-30 parts of a dispersant and 0.1-2.0 parts of an emulsifier; wherein the crystal morphology regulator is selected from at least one of an organic acid or an organic acid salt, the crystal growth inhibitor is selected from at least one of an inorganic metal salt of potassium, aluminum or iron, and the dispersant is selected from C 1 -C 4 At least one of alkyl monohydric or polyhydric alcohol, polyethylene glycol or polyvinyl alcohol, and the emulsifier is at least one of anionic surfactant or nonionic surfactant.
[0008] The present invention is further configured such that the crystal morphology regulator is selected from one or more of succinic acid, citric acid, ethylenediaminetetraacetic acid, potassium sodium tartrate, potassium oxalate or sodium citrate.
[0009] The present invention is further configured such that the crystal growth inhibitor is selected from one or more of aluminum sulfate, iron sulfate, potassium aluminum sulfate, aluminum chloride, iron chloride, iron nitrate or aluminum nitrate.
[0010] The present invention is further configured such that the dispersant is selected from one or more of ethanol, propylene glycol, 1,4-butanediol, polyethylene glycol or polyvinyl alcohol; wherein the molecular weight of the polyethylene glycol is 500-4000, and the molecular weight of the polyvinyl alcohol is 30,000-150,000.
[0011] The present invention is further configured that the emulsifier is selected from sodium dodecyl sulfate, gum arabic, C 12 -C 18 One or more of fatty acid potassium, Tween 80 or sodium alginate.
[0012] The invention provides a preparation method of the gypsum composite admixture, comprising the following steps: mixing a crystal morphology regulator and a crystal growth inhibitor solid in required mass parts, adding deionized water to dissolve them evenly, and preparing a mixed solution with a mixed solid concentration of 15-25%; then adding a dispersant and an emulsifier in required mass parts to the prepared mixed solution, homogenizing and emulsifying, and forming a nano-emulsion type composite solution; finally using a spray drying technology to treat at 70-90°C to prepare a solid nano-composite additive, and sealing and storing it for standby use.
[0013] The present invention also provides an α-type high-strength gypsum, whose raw material components include dihydrate gypsum and the above-mentioned gypsum composite admixture, and the added amount of the gypsum composite admixture is 0.5-2.0% of the mass of calcium sulfate dihydrate in the dihydrate gypsum.
[0014] The present invention is further configured such that the aspect ratio of the α-type high-strength gypsum is 1-3, and the absolute dry compressive strength is ≥50MPa.
[0015] The present invention also provides a method for preparing α-type high-strength gypsum, comprising the following steps:
[0016] (1) Take industrial by-product gypsum with a calcium sulfate dihydrate content of ≥90% and wash it with water until the pH is approximately neutral;
[0017] (2) Mixing the washed dihydrate gypsum with water and stirring to prepare a gypsum slurry with a solid content of 15-25%, and adding the above-prepared gypsum composite admixture according to 0.5-2.0% of the mass of calcium sulfate dihydrate, and mixing it evenly with the gypsum slurry;
[0018] (3) adding the above gypsum slurry into a hydrothermal reactor and reacting at a hydrothermal temperature of 125-135°C and a hydrothermal time of 3-5 hours;
[0019] (4) After the reaction is completed, solid-liquid separation and drying are carried out to obtain a high-strength gypsum product.
[0020] The present invention has the following beneficial effects: the gypsum composite admixture of the present invention is used to prepare high-strength gypsum, which promotes the growth of high-strength gypsum crystal particles in a single crystal manner, avoids cross-growth between crystals, and obtains a well-developed, smooth-looking high-strength gypsum product, and the obtained high-strength gypsum product has uniform and small particle sizes and an absolute dry compressive strength of ≥50MPa; and by using the gypsum composite admixture of the present invention, the preparation process of high-strength gypsum is less affected by fluctuations in external working conditions, and the product performance can be kept stable during continuous operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the high-strength gypsum prepared in Example 1.
[0022] Figure 2 This is a scanning electron microscope image of the high-strength gypsum prepared in Comparative Example 1.
[0023] Figure 3 This is a scanning electron microscope image of the high-strength gypsum prepared in Comparative Example 3. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by professionals in this field based on the content of the present invention still belong to the scope of protection of the present invention.
[0025] Example 1
[0026] 1. Preparation of gypsum composite admixture
[0027] In this embodiment, the raw material components of the gypsum composite admixture include, by weight, 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 30 parts of 1,4-butanediol and 0.1 parts of sodium dodecyl sulfate. The preparation of the gypsum composite admixture includes the following steps:
[0028] (1) Mixing given weight parts of ethylenediaminetetraacetic acid, citric acid and ferric chloride solids, adding deionized water to dissolve them uniformly, and preparing a mixed solution with a mixed solid concentration of 20%;
[0029] (2) adding given weight parts of 1,4-butanediol and sodium dodecyl sulfate to the mixed solution prepared in step (1), and homogenizing and emulsifying the mixed solution at 2500 r / min using a high-speed stirrer to form a nanoemulsion composite solution;
[0030] (3) The obtained nanoemulsion composite solution is treated at 80° C. using a spray drying technique to prepare a solid nanocomposite additive, which is then sealed and stored for later use.
[0031] (II) Preparation of α-type high-strength gypsum
[0032] The steps include:
[0033] (1) Take industrial by-product gypsum with a calcium sulfate dihydrate content greater than 90% and wash it with water until the pH is approximately neutral;
[0034] (2) Mixing the washed dihydrate gypsum with water and stirring to prepare a gypsum slurry with a solid content of 20%, and adding the above-prepared gypsum composite admixture according to 1.0% of the mass of calcium sulfate dihydrate, and mixing it evenly with the gypsum slurry;
[0035] (3) The gypsum slurry with the gypsum composite admixture added in step (2) was added into the hydrothermal reactor, and the stirring speed was controlled to be 400 r / min, the hydrothermal temperature to be 135°C, and the hydrothermal time to be 3 h.
[0036] (4) After the reaction is completed, solid-liquid separation and drying are carried out to obtain a high-strength gypsum product.
[0037] The obtained high-strength gypsum product was characterized by SEM. Figure 1 As shown in the figure, the prepared α-type high-strength gypsum product has a small degree of agglomeration between crystals, good dispersion, a narrow distribution range of the aspect ratio of single crystal particles (1-2), and good uniformity. The absolute dry compressive strength of the prepared high-strength gypsum product was tested, referring to JC / T 2038-2010 "α-type high-strength gypsum", the test process is: first prepare the test piece, the preparation process of the test piece is: add the prepared high-strength gypsum powder to the appropriate amount of hydration water, the consistency is 30%-40%, stir for about 15-30s, pour the fluid with appropriate consistency into the cement test mold (specification: 10*10*40mm-six-link), so that the fluid slightly overflows the test mold, and then lift the left and right ends 1-2cm high, so that the test mold falls freely to remove the bubbles, repeat 10-15 times until there are no obvious bubbles, and then use a scraper to gently scrape off the surface overflow, let it stand for 2-4h, remove the mold and remove the test piece, place it at room temperature for 24h, place it in a 40±5℃ oven for 24-48h, take out the test piece, dry it and store it; then use CTM9100 universal testing machine to test the compressive strength of the test piece to obtain the absolute dry compressive strength value. In this embodiment, the absolute dry compressive strength of the high-strength gypsum prepared in this step is 57 MPa.
[0038] (III) Stability test under different working conditions
[0039] The absolute dry compressive strength of the high-strength gypsum products prepared under different working conditions was tested. The preparation method and strength test method of the high-strength gypsum were the same as those in the above (II) preparation of high-strength gypsum. Five parallel experiments were set up to control the working conditions of the hydrothermal reaction to fluctuate within a certain range to examine the impact on product quality and stability. The reaction temperature fluctuated at 130±5℃, and the reaction time fluctuated at 3-5h. The hydrothermal reaction conditions of the five parallel experiments and the strength values of the high-strength gypsum products are statistically shown in Table 1.
[0040] Table 1 Strength of high-strength gypsum products obtained under working condition fluctuations in Example 1
[0041]
[0042] As shown in Table 1, under fluctuating working conditions, the average absolute dry compressive strength of the high-strength gypsum product prepared in this embodiment is 59.2 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 2.71, indicating that the product quality of high-strength gypsum produced by the gypsum composite admixture prepared in this embodiment under fluctuating working conditions is relatively stable.
[0043] Example 2
[0044] 1. Preparation of gypsum composite admixture
[0045] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 30 parts of 1,4-butanediol and 1.0 part of sodium dodecyl sulfate.
[0046] (II) Preparation of α-type high-strength gypsum
[0047] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared in Example 2. The prepared α-type high-strength gypsum product has a small degree of agglomeration between crystals, good dispersibility, a narrow distribution range of the aspect ratio of single crystal particles, an aspect ratio of 1 to 2, good uniformity, and the prepared high-strength gypsum product has an absolute dry compressive strength of 56 MPa.
[0048] (III) Stability test under different working conditions
[0049] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 57 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 3.69.
[0050] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0051] Example 3
[0052] 1. Preparation of gypsum composite admixture
[0053] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 30 parts of 1,4-butanediol and 0.05 parts of sodium dodecyl sulfate.
[0054] (II) Preparation of α-type high-strength gypsum
[0055] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The obtained α-type high-strength gypsum product has slightly worse crystal dispersion and aspect ratio uniformity of single crystal particles than Examples 1 and 2, with an aspect ratio of 1 to 4, and the dry compressive strength of the prepared high-strength gypsum product is 53 MPa.
[0056] (III) Stability test under different working conditions
[0057] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 51.4 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 6.28.
[0058] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0059] Example 4
[0060] 1. Preparation of gypsum composite admixture
[0061] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 30 parts of 1,4-butanediol and 1.0 part of sodium alginate.
[0062] (II) Preparation of α-type high-strength gypsum
[0063] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The prepared α-type high-strength gypsum product has a small degree of agglomeration between crystals, good dispersibility, a narrow distribution range of the aspect ratio of single crystal particles, an aspect ratio of 1 to 2, good uniformity, and the prepared high-strength gypsum product has an absolute dry compressive strength of 61 MPa.
[0064] (III) Stability test under different working conditions
[0065] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 60 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 2.83.
[0066] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0067] Example 5
[0068] 1. Preparation of gypsum composite admixture
[0069] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 10 parts of 1,4-butanediol and 1.0 part of sodium alginate.
[0070] (II) Preparation of α-type high-strength gypsum
[0071] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The prepared α-type high-strength gypsum product has a small degree of agglomeration between crystals, good dispersibility, a narrow distribution range of the aspect ratio of single crystal particles, an aspect ratio of 1 to 2, good uniformity, and the prepared high-strength gypsum product has an absolute dry compressive strength of 57 MPa.
[0072] (III) Stability test under different working conditions
[0073] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 59.2 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 2.71.
[0074] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0075] Example 6
[0076] 1. Preparation of gypsum composite admixture
[0077] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 40 parts of 1,4-butanediol and 1.0 part of sodium alginate.
[0078] (II) Preparation of α-type high-strength gypsum
[0079] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The obtained α-type high-strength gypsum product, due to the slightly large amount of dispersant added, the contact effect between the dispersant and the crystal is weakened, so the crystal particles are in a state of agglomeration, the dispersion is poor, the aspect ratio of the single crystal particles ranges from 1 to 6, and the uniformity is reduced compared with Examples 4 and 5. The absolute dry compressive strength of the prepared high-strength gypsum product is 48MPa.
[0080] (III) Stability test under different working conditions
[0081] The testing method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 47.2 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 4.31.
[0082] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0083] Example 7
[0084] 1. Preparation of gypsum composite admixture
[0085] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 5 parts of 1,4-butanediol and 1.0 part of sodium alginate.
[0086] (II) Preparation of α-type high-strength gypsum
[0087] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared in this example. The prepared α-type high-strength gypsum product has particles in an agglomerated state, poor crystal dispersion, and a single crystal particle aspect ratio distribution range of 1 to 7. Compared with Examples 4 and 5, the uniformity is reduced, and the prepared high-strength gypsum product has an absolute dry compressive strength of 46 MPa.
[0088] (III) Stability test under different working conditions
[0089] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 48.6 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 5.78.
[0090] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0091] Example 8
[0092] 1. Preparation of gypsum composite admixture
[0093] Same as Example 1.
[0094] (II) Preparation of α-type high-strength gypsum
[0095] Compared with Example 1, the only difference is that the amount of the gypsum composite admixture added is different. In this embodiment, the gypsum composite admixture prepared above is added according to 2.0% of the mass of calcium sulfate dihydrate. The prepared α-type high-strength gypsum product has good crystal dispersion and uniformity of aspect ratio of single crystal particles, which is not significantly different from that of Example 1; the aspect ratio is 1-2, and the absolute dry compressive strength of the prepared high-strength gypsum product is 60MPa.
[0096] (III) Stability test under different working conditions
[0097] The testing method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 59 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 2.61.
[0098] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0099] Example 9
[0100] 1. Preparation of gypsum composite admixture
[0101] Same as Example 1.
[0102] (II) Preparation of α-type high-strength gypsum
[0103] Compared with Example 1, the only difference is that the amount of the gypsum composite admixture added is different. In this embodiment, the gypsum composite admixture prepared above is added according to 0.5% of the mass of calcium sulfate dihydrate. The prepared α-type high-strength gypsum product has good crystal dispersion and uniformity of aspect ratio of single crystal particles, which is not significantly different from that of Example 1; the aspect ratio is 1-2, and the absolute dry compressive strength of the prepared high-strength gypsum product is 59MPa.
[0104] (III) Stability test under different working conditions
[0105] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 57.4 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 2.15.
[0106] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0107] Example 10
[0108] 1. Preparation of gypsum composite admixture
[0109] Same as Example 1.
[0110] (II) Preparation of α-type high-strength gypsum
[0111] Compared with Example 1, the only difference is that the amount of the gypsum composite admixture added is different. In this embodiment, the gypsum composite admixture prepared above is added according to 0.2% of the mass of calcium sulfate dihydrate. The obtained α-type high-strength gypsum product has poorer crystal dispersion and uniformity of aspect ratio of single crystal particles than Example 9; the aspect ratio is 5-10, and the absolute dry compressive strength of the prepared high-strength gypsum product is 44MPa.
[0112] (III) Stability test under different working conditions
[0113] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 42.8 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 2.79.
[0114] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0115] Embodiment 11
[0116] 1. Preparation of gypsum composite admixture
[0117] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 20 parts of 1,4-butanediol and 1.0 part of sodium alginate.
[0118] (II) Preparation of α-type high-strength gypsum
[0119] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The prepared α-type high-strength gypsum product has good crystal dispersion, good uniformity of aspect ratio of single crystal particles, aspect ratio of 1 to 2, and the prepared high-strength gypsum product has an absolute dry compressive strength of 59 MPa.
[0120] (III) Stability test under different working conditions
[0121] The test method is the same as that in Example 1. In this example, the average strength of the high-strength gypsum products obtained by 5 groups of parallel experiments is 60 MPa, and the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 2.81.
[0122] In this embodiment, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0123] Example 12
[0124] 1. Preparation of gypsum composite admixture
[0125] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture include 20 parts of succinic acid, 20 parts of citric acid, 30 parts of aluminum sulfate solid, 10 parts of polyethylene glycol 1000 and 1.0 part of Tween 80 in parts by mass.
[0126] (II) Preparation of α-type high-strength gypsum
[0127] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The prepared α-type high-strength gypsum product has basically no agglomeration between crystal particles, good dispersibility, and a distribution range of aspect ratio of single crystal particles of 1 to 2, with good uniformity. The prepared high-strength gypsum product has an absolute dry compressive strength of 59 MPa.
[0128] In this embodiment, the strength test method of high-strength gypsum is the same as that in Embodiment 1.
[0129] Example 13
[0130] 1. Preparation of gypsum composite admixture
[0131] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by mass, include 10 parts of potassium sodium tartrate, 20 parts of potassium oxalate, 25 parts of potassium aluminum sulfate, 20 parts of glycerol and 0.5 parts of gum arabic.
[0132] (II) Preparation of α-type high-strength gypsum
[0133] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared in this example. The prepared α-type high-strength gypsum product has basically no agglomeration between crystal particles, good dispersibility, and the aspect ratio distribution range of single crystal particles is 1-2, with good uniformity. The prepared high-strength gypsum product has an absolute dry compressive strength of 60 MPa.
[0134] In this embodiment, the strength test method of high-strength gypsum is the same as that in Embodiment 1.
[0135] Embodiment 14
[0136] 1. Preparation of gypsum composite admixture
[0137] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by weight, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride, 15 parts of polyvinyl alcohol (molecular weight: 30,000) and 0.5 parts of palm oil fatty acid potassium soap.
[0138] (II) Preparation of α-type high-strength gypsum
[0139] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The prepared α-type high-strength gypsum product has basically no agglomeration between crystal particles, good dispersibility, and a distribution range of aspect ratio of single crystal particles of 1 to 2, with good uniformity. The prepared high-strength gypsum product has an absolute dry compressive strength of 58 MPa.
[0140] In this embodiment, the strength test method of high-strength gypsum is the same as that in Embodiment 1.
[0141] Comparative Example 1
[0142] 1. Preparation of gypsum composite admixture
[0143] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by weight, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride and 30 parts of 1,4-butanediol, and no emulsifier is added.
[0144] (II) Preparation of high-strength gypsum
[0145] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The high-strength gypsum product obtained has a morphology as follows: Figure 2 As shown, the crystal dispersion is close to that of Example 3, the aspect ratio uniformity of the single crystal particles is poor, the aspect ratio is 2-3, and the absolute dry compressive strength of the prepared high-strength gypsum product is 52 MPa.
[0146] (III) Stability test under different working conditions
[0147] The test method is the same as that in Example 1. In this example, the hydrothermal reaction conditions of 5 groups of parallel experiments and the strength values of the high-strength gypsum products are statistically shown in Table 2. The average strength value of the high-strength gypsum products obtained by the 5 groups of parallel experiments is 50.2 MPa.
[0148] Table 2 Strength of high-strength gypsum products obtained under working condition fluctuations in Comparative Example 1
[0149]
[0150] Although the strength value of the obtained high-strength gypsum product is ≥50MPa, the mean square deviation of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 6.43, indicating that the quality of the gypsum products produced under fluctuating working conditions is unstable.
[0151] In this comparative example, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0152] Comparative Example 2
[0153] 1. Preparation of gypsum composite admixture
[0154] Compared with Example 4, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by weight, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid, 35 parts of solid ferric chloride and 1.0 part of sodium alginate, and no dispersant is added.
[0155] (II) Preparation of high-strength gypsum
[0156] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared in this example. The obtained high-strength gypsum product has poor crystal dispersion, the crystal particles are in a state of agglomeration, the aspect ratio uniformity of the single crystal particles is average, the aspect ratio is 1-2, and the dry compressive strength of the prepared high-strength gypsum product is 47MPa.
[0157] (III) Stability test under different working conditions
[0158] The test method is the same as that in Example 1. In this example, the hydrothermal reaction conditions and the strength values of the high-strength gypsum products of the five parallel experiments are statistically shown in Table 3. The average strength of the high-strength gypsum products obtained by the five parallel experiments is 48.6 MPa, and the mean square error of the absolute dry compressive strength data of the high-strength gypsum products obtained between the groups is 5.39. The absolute dry compressive strength of the prepared high-strength gypsum product is less than 50 MPa, which does not meet the requirements of the high-strength gypsum compressive strength.
[0159] Table 3 Strength of high-strength gypsum products obtained under working condition fluctuations in Comparative Example 2
[0160]
[0161] In this comparative example, the strength test method of high-strength gypsum in the above processes (ii) and (iii) is the same as that in Example 1.
[0162] Comparative Example 3
[0163] 1. Preparation of gypsum composite admixture
[0164] Compared with Example 1, the only difference is that the raw material components for preparing the gypsum composite admixture are different. In this embodiment, the raw material components of the gypsum composite admixture, by weight, include 30 parts of ethylenediaminetetraacetic acid, 10 parts of citric acid and 35 parts of solid ferric chloride, and no emulsifier and dispersant are added.
[0165] (II) Preparation of high-strength gypsum
[0166] Compared with Example 1, the only difference is that the gypsum composite admixture used is the gypsum composite admixture prepared as described above in this Example. The high-strength gypsum product obtained has a morphology as follows: Figure 3As shown, the crystal dispersion is poor, the particles are in a state of agglomeration, the aspect ratio uniformity of the single crystal particles is poor, the aspect ratio is 4-8, and the absolute dry compressive strength of the prepared high-strength gypsum product is 45.6MPa. The absolute dry compressive strength is less than 50MPa, which does not meet the requirements of the high-strength gypsum compressive strength.
[0167] In this comparative example, the strength test method of high-strength gypsum is the same as that in Example 1.
[0168] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A gypsum composite admixture, characterized in that: The method comprises the following raw material components in parts by weight: 30-50 parts of a crystal morphology regulator, 25-45 parts of a crystal growth inhibitor, 10-30 parts of a dispersant and 0.1-2.0 parts of an emulsifier; Among them, the crystal morphology regulator is selected from at least one of organic acids or organic acid salts, the crystal growth inhibitor is selected from at least one of inorganic metal salts of potassium, aluminum or iron, the dispersant is selected from at least one of C1-C4 alkyl monohydric or polyhydric alcohols, polyethylene glycol or polyvinyl alcohol, and the emulsifier is selected from at least one of anionic surfactants or non-ionic surfactants.
2. The gypsum composite admixture according to claim 1, characterized in that: The crystal morphology regulator is selected from one or more of succinic acid, citric acid, ethylenediaminetetraacetic acid, potassium sodium tartrate, potassium oxalate or sodium citrate.
3. The gypsum composite admixture according to claim 1, characterized in that: The crystal growth inhibitor is selected from one or more of aluminum sulfate, iron sulfate, potassium aluminum sulfate, aluminum chloride, iron chloride, iron nitrate or aluminum nitrate.
4. The gypsum composite admixture according to claim 1, characterized in that: The dispersant is selected from one or more of ethanol, glycerol, 1,4-butanediol, polyethylene glycol or polyvinyl alcohol, wherein the molecular weight of the polyethylene glycol is 500-4000, and the molecular weight of the polyvinyl alcohol is 30,000-150,000.
5. The gypsum composite admixture according to claim 1, characterized in that: The emulsifier is selected from sodium dodecyl sulfate, gum arabic, C 12 -C 18 One or more of fatty acid potassium, Tween 80 or sodium alginate.
6. An α-type high-strength gypsum, characterized in that: The raw material components include dihydrate gypsum and the gypsum composite admixture described in any one of claims 1 to 5, and the added amount of the gypsum composite admixture is 0.5 to 2.0% of the mass of calcium sulfate dihydrate in the dihydrate gypsum.
7. The α-type high-strength gypsum according to claim 6, characterized in that: The aspect ratio is 1~3, and the absolute dry compressive strength is ≥50MPa.
Citation Information
Patent Citations
Method for preparing shape-controlled alpha-semi-hydrated gypsum by using flue gas desulfurized gypsum
CN101113084A
Preparation method for cellulose crystal susceptible to re-dispersion after drying
CN103275336A
Preparation method of large particle size calcium sulphate dihydrate in wet-process phosphoric acid technology
CN106395879A
Method for preparing high-whiteness short-column submicron-scale alpha-hemihydrate gypsum by using desulfurized gypsum
CN109704605A
Method of efficiently leaching valuable metal impurities in phosphogypsum and preparing high-value-added gypsum products
CN111560521A